2021
DOI: 10.1186/s42358-021-00207-2
|View full text |Cite
|
Sign up to set email alerts
|

Ultrasonographic and resistance index evaluation of nails in psoriatic arthritis, psoriasis, and control groups: a cross-sectional study

Abstract: Background Nail psoriasis occurs frequently in patients with psoriatic disease, it can lead to functional impairment, pain, discomfort, decreased quality of life and can also be a predictor for the development of arthritis. Early recognition of this condition can provide early and effective treatment and prevent structural impairment. This study aims to identify nail ultrasonographic characteristics in three groups: psoriasis (PsO), psoriatic arthritis (PsA) and controls patients, to determine … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
11
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(18 citation statements)
references
References 42 publications
5
11
0
2
Order By: Relevance
“…The only parameter of little use was the distance from the center of the distal phalange to the nail plate, which varied with age, sex, hallux, weight, and nail consistency. This parameter, known as nail bed thickness, was analyzed by other authors, who found ranges of measure lower than those in this study (Cecchini et al, 2009;De Rossi et al, 2021;Idolazzi et al, 2018;Idolazzi et al, 2019;Marina et al, 2016;Mondal et al, 2018;Naredo et al, 2019;Wortsman et al, 2004;Wortsman & Jemec, 2006). However, none of these studies used the toenail unit as a model or made comparisons in healthy participants, and therefore, comparative analysis may not be appropriate.…”
Section: Resultsmentioning
confidence: 59%
See 2 more Smart Citations
“…The only parameter of little use was the distance from the center of the distal phalange to the nail plate, which varied with age, sex, hallux, weight, and nail consistency. This parameter, known as nail bed thickness, was analyzed by other authors, who found ranges of measure lower than those in this study (Cecchini et al, 2009;De Rossi et al, 2021;Idolazzi et al, 2018;Idolazzi et al, 2019;Marina et al, 2016;Mondal et al, 2018;Naredo et al, 2019;Wortsman et al, 2004;Wortsman & Jemec, 2006). However, none of these studies used the toenail unit as a model or made comparisons in healthy participants, and therefore, comparative analysis may not be appropriate.…”
Section: Resultsmentioning
confidence: 59%
“…De Rossi et al (2021) showed a relation between age and some ultrasound parameters, including nail plate and bed thickness. However, most of the results obtained here do not support this relation, not even concerning nail plate thickness, as the only parameter that varied with age in the present study was the distance from the center of the distal phalange to the nail plate.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…В целом ряде ранее опубликованных исследований было показано, что под влиянием системной терапии псориаза ацитретином, циклоспорином, адалимумабом и этанарцептом происходит уменьшение плотности и размеров сосудистых клубочков и снижение уровня допплеровского кровотока в коже и ногтях больных псориазом, также продемонстрировано влияние системной терапии на плазменные концентрации VEGF [6,12,13,[16][17][18][19][20][21][22][23]. Следует отметить, что большинство из этих работ выполнены на небольшой выборке больных, в них использовался только один из методов визуализации ангиогенеза кожи (либо видеодерматоскопия, либо ультразвуковая допплерография).…”
Section: Discussionunclassified
“…Позитивной особенностью применения энергетического ультразвукового допплеровского исследования является возможность визуализации артериальных сосудов ногтевого ложа [19,20]. В ряде работ у больных псориазом продемонстрированы повышение количества допплеровских сигналов в слое дермы в области псориатической бляшки и ногтевом ложе при псориатическом поражении ногтей, изменения характера кровотока в артериях ногтевого ложа с повышением индекса резистивности [21][22][23].…”
Section: обоснованиеunclassified